Abiotic stresses and ways to overcome them on Achillea millefolium L. in conditions of the Western Precaucasus - R. R. Tkhaganov; A. I. Morozov; N. S. Tropina; R. N. Tkhaganov (Овощи России, 2022)
Relevance. An important place in the extensive assortment of ether-oil cultures belongs to the common yarrow (Achillea millefolium L.), phytopreparations produced on its basis are widely used in the treatment of inflammatory processes, the normalization of the gastrointestinal tract.Methodology. To provide the pharmaceutical industry with this type of medicinal raw materials, it is necessary to create adapted technologies, where an important link will be the development of techniques for adapting the culture to unstable weather conditions.Results. The studies were carried out in the conditions of the North Caucasus branch of VILAR (West Ciscaucasia) in 2019-2021, by conducting small-scale experiments. The indicators of growth and development of yarrow of the II-V years of vegetation, the yield of raw materials, the content of essential oil and its collection per hectare under unstable weather conditions were studied. It was found that with sufficient moisture supply and a comfortable level of air temperatures in 2021, a high yield of medicinal raw materials of this crop is observed. At the same time, low water supply and high temperatures in 2020 had a negative impact on plant development, a drop in yield of 1.35-1.65 t/ha was established, which led to losses in the collection of essential oil per hectare by 3.23-4.32 kg/ha. A decrease in the degree of negative impact of drought on yarrow plants of the II-IV years of vegetation was achieved through the use of silicon-containing microfertilization Siliplant. Double treatment with this drug contributed to a decrease in the yield of raw materials to 5-6% and the collection of essential oil per hectare to 5-7%. in the control – 21-24% and 22-24%, respectively. Despite the high yield of raw materials in the III-III years of yarrow vegetation, the use of Siliplant allows collecting ether-oil raw materials for 4 years. Thus, the inclusion of Siliplant microfertilization in cultivation technology allows plants to adapt to hydrothermal stress conditions and makes it possible to obtain stable yields of raw materials with a high collection of essential oil per hectare, regardless of weather conditions.